Più veloce della gravità - Bagnoli, Franco (Il Colle di Galileo, 2018)
In teaching physics one works hard to make pupils understand that all masses fall with the same acceleration. However, if we drop compound bodies, some parts of them can actually “go faster” than free fall. This experiment can be easily accomplished with a chain and a dumbbell. Here we try to provide a simple explanation for this apparently impossible effect.